Podnebni tipi v Sloveniji - Ogrin, Darko (Geografski vestnik, 1996)
The article discusses the types of climate in Slovenia. As the basis for climate division was taken the Köppen climate system, according to which three basic climate types occur in Slovenia: the temperate humid climate with hot summers (Cfa), the temperate humid climate with warm summers (Cfb), and the mountainous climate (H). These basic types are further divided into nine subtypes, as to the precipitation regime, average temperatures of the coldest and the warmest months, and the ratio between the October and the April temperatures.
Keywords: climate; climatology; fizična geografija; klimatogeografija; klimatologija; physical geography; podnebje; Slovenia; Slovenija